2015
DOI: 10.17221/8532-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caprylic acid and Yucca schidigera extract on growth performance, relative organ weight, breast meat quality, haematological characteristics and caecal microbial shedding in mixed sex Ross 308 broiler Dickens

Abstract: Caprylic acid (CA) and Yucca schidigera (YS) extract have many functional and nutritional properties that may have applications in animal nutrition. These beneficial effects include improvement of growth performance, immunity and anti-microbial activity. This study was conducted to assess the effects of dietary supplementation with CA and YS extract on growth performance, relative organ weight, meat quality, blood characteristics and caecal microbial shedding in broilers. In total, 672 one-day-old Ross 308 (BW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Also, these results are in harmony with those obtained by Begum et al (2015) who reported that no significant differences were observed in total protein or RBCs with supplementation of MCFAs, while, had higher WBCs compared with the control group. Moreover, broilers fed the MCFAs diet exhibited increased lymphocyte counts compared with the control diets.…”
Section: Blood Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Also, these results are in harmony with those obtained by Begum et al (2015) who reported that no significant differences were observed in total protein or RBCs with supplementation of MCFAs, while, had higher WBCs compared with the control group. Moreover, broilers fed the MCFAs diet exhibited increased lymphocyte counts compared with the control diets.…”
Section: Blood Parameterssupporting
confidence: 90%
“…Previously, aromabiotic was shown to be effective against a wide range of opportunistic microorganisms, including E. coli (Khosravinia, 2015), Salmonella (Van Immerseel et al, 2004), Campylobacter and Clostridia (Hermans et al, 2011) which are more harmful to broiler performance in stressful conditions. On other hand Begum et al (2015) found that E. coli counts were reduced with MCFAs diet (6.62 log 10 cfu/g) when compared with the control diet.…”
Section: Intestinal Microfloramentioning
confidence: 89%
See 1 more Smart Citation
“…There are now studies available combining YSE with other additives such as caprylic acid (Wang & Kim 2011;Begum et al 2015), coccidiostat (Alfaro et al 2007), zeolite (Çabuk et al 2004), yeast cell walls (Gurbuz et al 2011), or coccidiosis vaccine (Alfaro et al 2007), to explore their potentials in improving the performance of livestock. Our results showed that YSE alone exhibited greatest potentials in the finisher phase of broilers, which gives us a cue to explore the combining effects of YSE and other additives, to see if they could improve the productivity of animals in a wider range of time.…”
Section: Discussionmentioning
confidence: 99%
“…The use of phytogenic feed additives such as Y. shidigera containing steroidal saponins was found to improve intestinal health, reducing microbial pressure and stabilizing bowel health while preventing intestinal disorder, which could lead to improved nutrient digestibility and absorption [ 17 ]. The intestinal presence of saponins has previously been shown to influence the permeability of the membrane and the cellular transport of molecules such as macromolecules.…”
Section: Discussionmentioning
confidence: 99%